If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 13y = 5y + -40 Reorder the terms: 2 + 13y = -40 + 5y Solving 2 + 13y = -40 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 2 + 13y + -5y = -40 + 5y + -5y Combine like terms: 13y + -5y = 8y 2 + 8y = -40 + 5y + -5y Combine like terms: 5y + -5y = 0 2 + 8y = -40 + 0 2 + 8y = -40 Add '-2' to each side of the equation. 2 + -2 + 8y = -40 + -2 Combine like terms: 2 + -2 = 0 0 + 8y = -40 + -2 8y = -40 + -2 Combine like terms: -40 + -2 = -42 8y = -42 Divide each side by '8'. y = -5.25 Simplifying y = -5.25
| 33x+4=55(7) | | 4+2n=20 | | 4x^2y^3+8x^4y^3-12x^2y^5= | | 12h-10h= | | 6x+3(2x-8)=31+x | | 2(a+b)=2a+2b | | 2x+3-x-1=x+2 | | 15x-7x=64 | | 3x-8+x=7x+4 | | 15x-7v=64 | | (4x+2)-(-3x-5)=3 | | 10b-3=20 | | 15x-4=9x-14 | | 3x-8+x=7x | | 13-a=3 | | 8-7x=160-35x | | 26*1=26 | | 0.5(a-0.5)=2-a | | 5x+4p=20 | | 5m+2(m+2)=(2m+15) | | -y-6y-9= | | 6x^3+15x^2= | | 9r+15=85 | | -2/7=4-r/3-10 | | 14d-2d=-42.7 | | 32-x=-4x+7 | | -7k-3-1= | | 1.4=0.04x-78.80 | | 0=-5-r/6-7 | | -5y+2x=-10 | | 816=342+x | | 46=-1+8x+18x+5 |